Stranded Whole Transcriptome RNA‐Seq for All RNA Types. (20th January 2015) - Miller, David F.B.; Yan, Pearlly X.; Fang, Fang; Buechlein, Aaron; Ford, James B.; Tang, Haixu; Huang, Tim H.; Burow, Matthew E.; Liu, Yunlong; Rusch, Douglas B.; Nephew, Kenneth P.
Abstract: Stranded whole transcriptome RNA‐Seq described in this unit captures quantitative expression data for all types of RNA including, but not limited to, miRNA (microRNA), piRNA (Piwi‐interacting RNA), snoRNA (small nucleolar RNA), lincRNA (large non‐coding intergenic RNA), SRP RNA (signal recognition particle RNA), tRNA (transfer RNA), mtRNA (mitochondrial RNA), and mRNA (messenger RNA). The size and nature of these types of RNA are irrelevant to the approach described here. Barcoded libraries for multiplexing on the Illumina platform are generated with this approach but it can be applied to other platforms with a few modifications. © 2015 by John Wiley & Sons, Inc.